PENGARUH KOMITMEN ORGANISASIONALDAN DUKUNGAN TIM KERJA TERHADAP REPRESENTASI EKSTERNAL POSITIF KARYAWAN DI TEMPAT KERJA - Widari, Intan Maharani; Wibawa, Made Artha (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
This research aimed to determine the influence of organizational commitment, and teamwork support towards a positive employee external representation research on the frontline employees ? McD in Denpasar Bali. The population in this study is 50 employees. The sampling method in this research  using saturated sample. All members of the population in this study use as a respondents because the population is small only 50 people. Thetool  analysis used is multiple linear regression analysis. The results in this study obtained the effect of organizational commitment is positive but not significant toa  positive employee external representation, and teamwork support have a significant positive effect on positive employee  external representation.